2017
DOI: 10.1186/s12905-017-0420-0
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility of self-reported age at menarche: The Tromsø Study

Abstract: BackgroundPrevious studies of the reproducibility of self-reported age at menarche have been limited because of small study samples, short follow-up and the limited age span of the women included.MethodsThe present study assessed the reproducibility of age at menarche in 6731 women with a wide variation of age when giving the information about age at menarche. The women reported age at menarche in a self-administered questionnaire, both in 1986–1987 and 1994–1995. They were all residents of Tromsø, Norway, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Therefore, while it reduces our ability to detect modification of radiation risks, we do not believe that having incomplete data resulted in biased risk estimates. Reproductive history was self-reported, although such information is typically reported reliably (47,48) and recall bias is unlikely. Another possible limitation is lack of data on expression of estrogen (ER), progesterone (PR) and human epidermal growth factor receptors (HER2) that define several biologically distinct subtypes of breast cancer (49)(50)(51).…”
Section: Effects Of Reproductive and Other Factors On Radiation Risksmentioning
confidence: 99%
“…Therefore, while it reduces our ability to detect modification of radiation risks, we do not believe that having incomplete data resulted in biased risk estimates. Reproductive history was self-reported, although such information is typically reported reliably (47,48) and recall bias is unlikely. Another possible limitation is lack of data on expression of estrogen (ER), progesterone (PR) and human epidermal growth factor receptors (HER2) that define several biologically distinct subtypes of breast cancer (49)(50)(51).…”
Section: Effects Of Reproductive and Other Factors On Radiation Risksmentioning
confidence: 99%
“…However, larger population-based studies following similar designs and conducted in different geographical areas within Norway should be carried out to explore how the trend of pubertal timing develops in Norway. (58,65,66,78,(187)(188)(189)(190)(191)(192)(193)(194). Open markers are retrospective surveys in adult women.…”
Section: Pubertal References Compared To Current Referencesmentioning
confidence: 99%
“…Previous studies have found moderate to high agreement of age at menarche as reported in adulthood with the true age at menarche. 38 , 39 BMI at the time of menarche could be a confounder. Although it was not possible to measure BMI near the time of menarche, a sensitivity analysis that included current BMI as a covariate did not change the results.…”
Section: Discussionmentioning
confidence: 99%